Introduction: Exploring Forgiveness in Nineteenth‐Century Poetry. Issue 2 (February 2014) - Mason, Emma
Abstract This essay serves as an introduction to the essays collected in the 'Nineteenth‐century Poetry and Forgiveness' cluster. It takes as its foundation the recent turn to questions of hospitality, forgiveness and gift in the intra‐disciplinary field of religion, philosophy and literature and highlights the centrality of these issues for reading nineteenth‐century poetry. The essay argues that nineteenth‐century poetry attempts to figure forgiveness as poetic sound and rhythm as a way of thinking reciprocal forgiving relationships between people. Part I contextualizes this argument and argues for an understanding of forgiveness through emotion. Part II offers an overview of the field of forgiveness scholarship and explores its relevance for nineteenth‐century debate on the topic. Part III offers a way into thinking forgiveness as sound and rhythm in Wordsworth's poem 'Airey‐Force Valley' through Martin Heidegger's reading of poetics and being.